The Diet Patterns of Diabetes Mellitus Patients in Lhokseumawe, Aceh Province, Indonesia - Haris, Zulfan; Nasution, Siti Zahara; Siregar, Cholina Trisa (Talenta Publisher, 2020)
Diabetes Mellitus/DM is an increase in blood glucose levels or hyperglycemia which causes various complications in some important organs such as eyes, kidneys, nerves, and blood vessels. A proper diet of diabetes mellitus patients is determined based on the amount of food intake, scheduled meal, and daily food composition. This study is a descriptive research, and aim to identify the diets of diabetic patients in Pusong, Lhokseumawe with 108 in population. The number of research samples were 52 respondents using purposive sampling techniques.Â The sample criteria applied with several conditions, such as had been suffering from type 2 DM for more than 5 years and able to read and write in Indonesian. Data were collected using a validated and reliable questionnaire with a Cronbach alpha test value of 0.841. The results showed that 78.8% of respondents were not able to control the type of daily food consumption, 73.1% were not able to control the amount of daily food, 67.3% were not able to obey the scheduled meal and 72.2% of the respondents were adhere to a daily diet. According to this research result, it is important to identify the factors that contribute to the diet of patients with diabetes mellitus in the future. Keywords: diabetes mellitus diet, blood glucose, hyperglycemia